Uses of Arterial Stiffness in Clinical Practice - Wilkinson, Ian B; Mäki-Petäjä, Kaisa M; Mitchell, Gary F (Arteriosclerosis, thrombosis, and vascular biology, 2020)
As far back as the ancient Egyptians and Greeks, physicians have observed and interpreted the arterial pulse to diagnose disease. In the last 20 years, advances in modern engineering have rendered quantitative pulse wave analysis widely available, reliable, and reproducible. To date, measurement of arterial stiffness has remained almost exclusively a research activity. However, ongoing technological improvements coupled with already strong and growing evidence of clinical value should facilitate integration of arterial stiffness measures into clinical practice in the near future. This brief review will highlight clinical areas where arterial stiffness measures are likely to be the most informative in clinical practice.